2018
DOI: 10.1016/j.dib.2018.03.093
|View full text |Cite
|
Sign up to set email alerts
|

Data on the effect of lead concomitant noise on oxidative stress in rats

Abstract: Exposure to chemical and physical factors occur in many occupations. Exposure to ambient pollutants such as noise, heavy metals, drugs enhance free radicals and can cause oxidative stress. The aim of the present project was to investigate noise and lead as two workplace stressors in rats. 20 male rats were assigned into 4 groups randomly. Rats in control group was not exposed to any stressor agent, while the first group was exposed to noise (105 dB, 4 kHz), the second group was exposed to lead acetate (gavage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…ROS may also indirectly induce the formation of DNA adducts by initiating autocatalytic lipid peroxidation, generating a large variety of potential genotoxic breakdown products, such as MDA [19]. Measurement of MDA levels in plasma or serum provide a convenient in vivo index of lipid peroxidation, and represent a non-invasive biomarker of oxidative stress [20].…”
Section: Discussionmentioning
confidence: 99%
“…ROS may also indirectly induce the formation of DNA adducts by initiating autocatalytic lipid peroxidation, generating a large variety of potential genotoxic breakdown products, such as MDA [19]. Measurement of MDA levels in plasma or serum provide a convenient in vivo index of lipid peroxidation, and represent a non-invasive biomarker of oxidative stress [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently several investigations have exercised the influence of combined exposure to noise and chemical substances. The impact of noise and organic solvent on non-auditory system was reported by several investigators (10)(11)(12)(13). Exposure to noise and xylene induced biochemical alterations in rat heart muscle (10).…”
Section: Introductionmentioning
confidence: 92%
“…Heavy metals such as arsenic, mercury, cadmium and lead are present in many forms in the environment and are widely present in number of industrial sectors. It has been reported that combined exposure of noise and lead induced oxidative stress in rat serum (13). Additionally, Conetta et al found that the co-exposure of noise and cadmium produced histological damage in rat heart muscle (7).…”
Section: Introductionmentioning
confidence: 99%
“…The testis is very sensitive to oxidative stress due to its unsaturated fatty acids ( 17 ). Noise and lead appear to cause oxidative stress in various tissues, including the testes, by disturbing the balance of the prooxidant/antioxidant system ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%